Paradoxical attenuation of neuroinflammatory response upon LPS challenge in miR-146b deficient mice - Chithanathan, Keerthana; Jürgenson, Monika; Guha, Mithu; Yan, Ling; Žarkovskaja, Tamara; Pook, Martin; Magilnick, Nathaniel; Boldin, Mark P.; Rebane, Ana; Tian, Li; Zharkovsky, Alexander (Frontiers in Immunology, 2022)
The miR-146 family consists of two microRNAs (miRNAs), miR-146a and miR-146b, which are both known to suppress immune responses in a variety of conditions. In this study, we described the expression of miR-146 family in microglial cells and studied the effect of miR-146b deficiency in neuroinflammation using wild-type (WT) and miR-146b deficient mice (Mir146b-/-) upon administration of lipopolysaccharide (LPS). We demonstrate that miR-146a is abundantly expressed in microglial cells, while miR-146b is expressed at lower level. Both miR-146a and miR-146b (miR-146a/b) were induced in response to LPS administration in microglial cells and in the hippocampal tissue of the adult mice. Interestingly, LPS induced sickness behavior was more dominant in WT mice as compared to Mir146b-/- mice. Accordingly, LPS challenge significantly increased the inflammatory status of microglia in WT mice, while Mir146b-/- mice showed less pronounced microglial activation. Similarly, microglia-mediated synaptic pruning was induced by LPS in WT mice but not in Mir146b-/- mice. Further gene expression analysis revealed that LPS induced stronger upregulation of pro-inflammatory cytokines in WT mice with simultaneous increase in anti-inflammatory cytokines in Mir146b-/- mice. In addition, reduced nuclear levels of the NF-κB protein in hippocampus, less reduction of miR-146 family target Irak1 and stronger upregulation of miR-146a was found in Mir146b-/- mice as compared to WT mice upon LPS challenge. Our results together show that Mir146b-/- mice have less signs of neuroinflammation upon LPS administration, which may be due to enhanced expression of miR-146a, which could downregulate inflammation in these mice as a potential compensation mechanism.